Experimental investigation on heat pipes as efficient heat transfer device / Mohd. Harisuddin Kusni - Kusni, Mohd. Harisuddin (2010)
An experimental study of heat transfer performance in varying angle heat pipe is carried out in this project. The heat pipe is designed to work in a closed evaporator-condenser system. The basic heat pipe differs from the thermosyphon in that a wick, constructed from a few layers of fine gauze. A vessel of heat pipe in its inner walls is lined with the wick structure. The heat pipe consists of a tube shell, wick structure and a working fluid. It has the ability to transport heat of working fluid through the hollow core by capillary action. The efficiency of heat pipe is related to the working fluid and its properties. Two copper heat pipes with the length of 0.35m have been fabricated in order to study the effect of performance by varying the orientation angles of heat pipe. One of the heat pipes functioned as thermosyphon and the other one have carbon fibre as wick material. Distilled water is used as the working fluid because of its cleanliness and free from microscopic contaminants. The thermal behavior of two vacuumed heat pipes which contain wick and without wick has been studied experimentally and analyzed. A comparison of temperature distribution at the outer wall of two heat pipes has been made for the angle of 0°, 10°, 20°, 30°, 60° and 90°. From the experiment, the data of the heat pipes such as heat supplied and heat dissipated are measured and collected. The efficiencies of two heat pipes are calculated.